Endoscopic pancreatic necrosectomy: why scuff when you can flush the muck – make it an easy row to hoe - Bansal, Rinkesh Kumar; Puri, Rajesh; Choudhary, Narendra S.; Bhatia, Sumit; Patel, Nisharg; Patle, Saurabh K.; Patil, Gaurav K.; Agarwal, Amit; Prabha, Chandra; Sud, Randhir (Endoscopy International Open, 2017)
Background and aims Endoscopic ultrasound (EUS) guided drainage of symptomatic pancreatic walled-off necrosis (WON) followed by fully covered self-expanding metal stent (FCSEMS) placement offers several advantages such as higher technical success rate and the option of necrosectomy. The aim of this study was to evaluate the safety and efficacy of EUS guided drainage of patients with WON by using FCSEMS and intracavitary lavage with a solution containing hydrogen peroxide and adopting a step-up approach.Methods A prospective open label study was carried out at a single tertiary care center between January 2014 and January 2016. Patients with symptomatic WON who underwent EUS guided drainage followed by FCSEMS placement were included. Primary end points were complete drainage with improvement in symptoms or major adverse events. Secondary end points were minor adverse events related to the procedures.Results A total of 64 patients (mean age 36 years; 52 males) were included. Technical success was achieved in 100 % of patients and clinical success was achieved in 90.6 %. Complete drainage was achieved with FCSEMS alone in 18 (28.1 %), FCSEMS with necrosectomy using lavage in 40 (62.5 %), FCSEMS with percutaneous drainage (PCD) in 5 (7.8 %), and 1 (1.6 %) patient required salvage surgery. The major adverse event was life threatening bleeding in 3 (4.7 %) patients. Minor adverse events were non-life threatening bleeding in 2 (3.1 %) patients and stent migration in 3 (4.7 %) patients. Conclusion EUS guided WON drainage with FCSEMS followed by necrosectomy with lavage using a solution containing hydrogen peroxide as a step-up approach is a minimally invasive and effective method with a high technical and clinical success rate. Patients with solid debris > 40 % need aggressive management.